Overexpression of CD6 and PD-1 Identifies Dysfunctional CD8+ T-Cells During Chronic SIV Infection of Rhesus Macaques - Enyindah-Asonye, Gospel; Nwankwo, Anthony; Rahman, Mohammad Arif; Hunegnaw, Ruth; Hogge, Christopher; Helmold Hait, Sabrina; Ko, Eun-Ju; Hoang, Tanya; Robert-Guroff, Marjorie (Frontiers in Immunology, 2020)
Effective CD8+ T-cell responses play an important role in determining the course of SIV/HIV viral infection. Here we identified a unique population of dysfunctional CD8+ T-cells in lymphoid tissues and bronchoalveolar lavage (BAL) of rhesus macaques with chronic SIV infection characterized by co-expression of CD6 and PD-1. The frequency of CD6 and PD-1 co-expressing CD8+ T-cells was significantly increased in lymphoid tissues and BAL during chronic SIV infection compared to pre-infection levels. These CD6+PD-1+CD8+ T-cells displayed impaired proliferation, cytokine secretion and cytotoxicity compared to their CD6-PD-1+CD8+ T cell counterparts. The frequency of CD8+PD-1+ and CD8+CD6-PD-1+ T-cells in the lymph node and bone marrow did not correlate with SIV viral load, whereas the frequency of CD8+CD6+PD-1+ T-cells positively correlated with SIV viral load in these tissues highlighting the contribution of CD6 to disease progression. CD6+PD-1+CD8+ T-cells expressed elevated levels of SHP2 phosphatase compared to CD6-PD-1+CD8+ T-cells providing a potential mechanism by which CD6 may induce T-cell dysfunction during chronic SIV infection. Combined targeting of CD6 and PD-1 effectively revived the CD8+ T-cell proliferative response in vitro suggesting a strategy for potential therapeutic benefit.